Overview Of Cakes Served At Traditional Marriage Ceremonies In Nagari Canduang Koto Laweh, Candung District, Agam Regency - Anisa Rahmawati; Wirnelis Syarif (Jurnal Pendidikan Tata Boga dan Teknologi, 2021)
This research was motivated by the researchers' curiosity about the accurate knowledge of the cakes served at the wedding ceremony at Nagari Canduang Koto Laweh. This type of research is descriptive research. Data observation techniques by means of observation, interviews and documentation. The results of this study indicate that the stages of the Nagari Canduang Koto Laweh wedding ceremony are starting from maresek to maantaan pabukoan. The types of cakes served are katan, ajik, pinyaram, kubang, timandi, bareh jao, batiah, pisang goreang, jaguang abuh, kue sapik and kue tangan. Cake recipe in the form of instructions which contain the name of the cake, ingredients and how to process the cake that will be served at the implementation of the wedding ceremony at Nagari Canduang Koto Laweh.